Analysis the Use of Binahong Leaf Extract (Anredera cordifolia) for the Wounds Itch Treatment (case for Islamic Boarding Schools Students) Ngembal Rejo, Kudus || Analisis Pemberian Daun Binahong (Anredera cordifolia) Terhadap Penyakit Luka Gatal Pada Siswa Pondok Pesantren, Ngembal Rejo, Kudus - Maula, Anis Hikmatul (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2021)
Binahong leaf (Anredera cordifolia) often known as maderia vine l eaves. Has many properties, namely as anti-inflammatory, antioxidant, antibacterial and anti-pain which is very important for the body. This property is supported by various ingredients in the leaves of binahong (A. cordifolia), in these leaves there are natural compounds in which there are flavonoids, saponins, tannins. With this content, there are many benefits of binahong leaves which are used by the village community as herbal medicine, one of which is as a healer for burns and wounds due to itching. Ancient people believed in a simple method to heal wounds caused by itching, this stdy uses direct observation in comparing the legs given collision of binahong leaves and those that do not. This study aims to prove the acceleration of wound closure with binahong leaves in a simple way.Daun binahong yang sering dikenal dengan dengan daun Maderia vine, banyak memiliki khasiat sebagai antiinflamasi, antioksidan, antibakteri serta antinyeri yang sangat penting bagi tubuh. Khasiat ini di dukung oleh berbagai kandungan dalam daun binahong (Anredera cordifolia) terdapat senyawa alami yang didalmnya meliputi flavonid, saponin, tanin. Dengan kandungan tersebut banyak manfaat dari daun binahong ini salah satunya dalah sebagai penyembuh luka bakar dan luka akibat gatal-gatal, di percaya orang zaman dahulu dengan metode sederhana untuk menyembuhkan luka akibat gatal-gatal. Penelitian ini bertujuan untuk membuktikan percepatan penutupan luka dengan daun binahong secara sederhana. Metode penelitian ini menggunakan pengamatan secara langsung (direct observation)